Peningkatan Kadar Serat Brownies Kukus dengan Penggunaan Tepung Kacang Merah (Phaseolus vulgaris L.) - Ompusunggu, Sandina Febryanti; Wisaniyasa, Ni Wayan; Rai Widarta, I Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i04.p21, 2023)
Brownies are a type of dark brown cake with a soft texture, a distinctive chocolate aroma and a sweet taste. Generally, flour-based brownies have a low fiber content. Therefore, red bean flour is expected to be used to increase fiber content. The purpose of this study was to determine the effect of using red bean flour on the fiber content of steamed brownies and produce steamed brownies with high fiber content and the best characteristics. This study used a completely randomized design (CRD) with the treatment ratio of wheat flour and red bean flour, namely: 100:0, 90:10, 80:20, 70:30, and 60:40 repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by Analysis of Variance (ANOVA), followed by the Duncan Multiple Range Test (DMRT). The results showed that the use of red bean flour had a significant effect (P<0.05) on crude fiber content, moisture content, ash content, protein content, fat content, carbohydrate content, and sensory properties of steamed brownies, but had no significant effect (P > 0.05) on the sensory properties of the color of steamed brownies. Treatment of 70 percent wheat flour and 30 percent red bean flour was the best treatment with 5.08 percent crude fiber content, 23.66 percent moisture content, 2.20 percent ash content, 8.84 percent protein content, 33.81 percent fat content, carbohydrate content of 31.46 percent with color, aroma, texture, taste and overall acceptance favored by the panelists.